GeSn-on-Si normal incidence photodetectors with bandwidths more than 40 GHz - Oehme, Michael; Kostecki, Konrad; Ye, Kaiheng; Bechler, Stefan; Ulbricht, Kai; Schmid, Marc; Kaschel, Mathias; Gollhofer, Martin; Koerner, Roman; Zhang, Wogong; Kasper, Erich; Schulze, Jörg (Optics Express, 2014)
GeSn (Sn content up to 4.2%) photodiodes with vertical pin structures were grown on thin Ge virtual substrates on Si by a low temperature (160 °C) molecular beam epitaxy. Vertical detectors were fabricated by a double mesa process with mesa radii between 5 μm and 80 μm. The nominal intrinsic absorber contains carrier densities from below 1·1016 cm -3 to 1·1017 cm-3 for Ge reference detectors and GeSn detectors with 4.2% Sn, respectively. The photodetectors were investigated with electrical and optoelectrical methods from direct current up to high frequencies (40 GHz). For a laser wavelength of 1550 nm an increasing of the optical responsivities (84 mA/W -218 mA/W) for vertical incidence detectors with thin (300 nm) absorbers as function of the Sn content were found. Most important from an application perspective all detectors had bandwidth above 40 GHz at enough reverse voltage which increased from zero to -5 V within the given Sn range. Increasing carrier densities (up to 1·1017 cm -3) with Sn contents caused the depletion of the nominal intrinsic absorber at increasing reverse voltages. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29